PEDAGOGICAL REQUIREMENTS FOR THE ORGANIZATION OF THE EDUCATIONAL PROCESS IN SPECIALIZED STATE EDUCATIONAL INSTITUTIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the pedagogical requirements for the organization of the educational process in state specialized educational institutions.